Recent Advances in the Synthesis and Application of Two‐Dimensional Zeolites. Issue 17 (20th July 2016) - Xu, Le; Sun, Junliang
Abstract : Two‐dimensional (2D) zeolites, originating from lamellar precursors, are a special kind of porous materials, in which crystalline zeolite nanolayers are weakly assembled in one particular direction. As there is no covalent‐bond between layers, the stacking sequences could be manipulated and possibly controlled to derive a family of zeolitic materials with structural diversity. The research on 2D zeolites arises from the primary casual discovery during traditional hydrothermal synthesis, which is followed by appropriate postsynthetic modifications to produce hierarchical lamellar zeolites. Recently, this area has experienced a remarkable evolution, which is highlighted by the rational synthesis of zeolite nanosheets by adopting a family of bifunctional surfactants and novel 3D zeolites through the "Assembly‐Disassembly‐Organization‐Reassembly" (ADOR) mechanism. Particularly, the direct construction of hierarchical lamellar zeolites with bifunctional surfactant is promising for industrial catalysis. Besides, an innovative top‐down method has demonstrated to be effective to produce novel types of 2D zeolites. Novel or even unfeasible zeolite topologies could be constructed by organizing and reassembling of the resulting layers. Here, the most attractive points achieved in the field of 2D zeolites are summarized, and the challenges and opportunities of zeolite chemistry associated with this type of porous materials are also proposed. Abstract : Two‐dimensional zeolites contain zeolite nanosheets assembled in one direction . Recent advances in the syntheses and applications of 2D zeolites are comprehensively reviewed. Particularly, the preparation of zeolite nanosheets with bifunctional surfactants and novel zeolite topology by utilizing the structure weakness is emphasized. Finally, the catalytic application and challenges for further research are also introduced.